Enhancing Administrative Efficiency Through Google Workspace: A Case Study At Pesantren Nurul Ikhlas Sidoarjo - Faizah, Rohmatul; Ramadhan, Fajar (CV. Inara, 2024)
This study aims to evaluate the impact of digitizing administration using some features of Google Workspace at Pondok Pesantren Nurul Ikhlas, Sidoarjo. This research emphasizes how the use of some Google Workspace features, namely Google Docs, Google Sheets, Google Drive, Google Meet, and Google Forms can improve the efficiency of pesantren administration. The research method used is a quantitative method with data collection through questionnaires and interviews with pesantren administrators and students. The results of the study are expected to show an increase in efficiency and effectiveness in managing pesantren administration after the implementation of Google Workspace.